Women in the Rural Areas Experience more Severe Menopause Symptoms - Yohanis, Mono (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: The aim of this study is to compare the severity of menopausal symptoms between menopause women who lived in urban area with those who lived in rural area. Methods: The study is conducted by comparing the scores of Menopause Rating Scale (MRS) and World Health Organization Quality of Life (WHOQOL) questionnaires of menopause women who lived in the City of Makassar with those who lived in rural areas of Selayar. Results: The results of the study revealed that menopausal symptoms are more severe on menopause women who lived in rural areas than those who lived in urban area. Less educated menopause women have more severe menopausal symptoms than those who have more education. Their Quality of Life show no significant difference. There is a correlation between the severity of menopausal symptoms with the quality of life of menopause women, the more severe the symptoms, the less the quality of life are. Conclusion: Menopausal symptoms are more severe on menopause women who lived in rural areas than those who lived in urban area. [Indones J Obstet Gynecol 2013; 37-2: 86-91] Keywords: menopausal symptoms, rural area, urban area